Integration of Tripartite Curriculum in PAI Learning through Digital Approach and Character Habitualization at Muhammadiyah Alam Surya Mentari Junior High School - Arya Adinata; Maksum, Muh. Nur Rochim (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
Islamic religious education in the era of digital disruption faces challenges in maintaining moral strengthening while adapting learning methods to the characteristics of generations who are familiar with technology. This study aims to analyze the tripartite curriculum integration strategy in the planning and implementation of Islamic Religious Education learning and describe the implementation of digital approaches and character habituation in shaping the independence and moral development of students at SMP Muhammadiyah Alam Surya Mentari Surakarta. This research uses a qualitative approach with a type of field research. Data was collected through interviews, observations, and documentation with informants of school principals, vice principals for curriculum, PAI teachers, and students. Data analysis uses the Miles and Huberman model through data reduction, data presentation, and Conclusion drawn. The results of the study show that curriculum integration is carried out through the integration of the Independent Curriculum, the ISMUBA curriculum, and the nature school curriculum which is implemented through experiential learning. The digital approach is used through interactive quizzes to increase student involvement, while character building is carried out through habituation of religious and social activities. This integration results in contextual learning and strengthens students' independence and morals.